Effects of rosin treatment on hygroscopicity, dimensional stability, and pore structure of round bamboo culm. (14th June 2021) - Su, Na; Fang, Changhua; Yu, Zixuan; Zhou, Hui; Wang, Xianke; Tang, Tong; Zhang, Shuqin; Fei, Benhua
Highlights: Natural rosin was used for the hydrophobic modification of bamboo culm. Rosin treatment improved the hydrophobicity and dimensional stability of bamboo culm. Rosin treatment decreased the porosity and total pore volume of bamboo. Abstract: Round bamboo culm maintains the natural texture, shape, and mechanical structure of raw bamboo materials compared with modern bamboo engineering materials, which break down bamboo culms into small elements. Promoting the use of round bamboo is an efficient and sophisticated way to utilize bamboo resources. However, the high hygroscopicity and poor dimensional stability are disadvantages that obstruct the utilization of round bamboo culm in construction and building applications. To solve these problem, rosin was used to modify the bamboo culm material in this work. The results show that the weight percentage gain of rosin was 9.98% after 8 h of impregnation. Part of the rosin formed transparent hydrophobic films on the surface of the bamboo culm, and decreased its surface wettability. Moreover, rosin was introduced into internal pores of bamboo where it decreased the porosity and total pore volume of bamboo by 14.42% and 23.81%, respectively. Additionally, the moisture absorption for 144 h at 65% relative humidity decreased by 39.27%, while rosin treatment decreased the swellings of wall thickness and diameter of bamboo culm from oven-dry to water saturation by 42.20% and 25.40%, respectively.